The Interference of Second Language Acquisition (English) on Third Language Acquisition (German) Learners in the Indian Context (L1-Indian Languages): The impact of second language acquisition on the word order in German for Indian learners in an ESL background (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The acquisition of second language influences greatly on the learners of third language acquisition. While acquiring a language, learners find difficulty in grammar and vocabulary. Insofar as there are distinct differences in word order at the syntactic level of German and English, the Indian learners of German as Foreign Language, coming from an ESL background, tend to commit repetitive errors in word order while writing sentences in German and such difficulties can be traced and used to advantage in a GFL context in the ESL background. This article is confined to patterns of sentences in German taught at the basic course in German. In this article the German sentences are correlated with English sentences. The findings of the article are relevant in the translation of both languages. It focusses only on the word order in German and English. The findings of the article are likely to help in the process of translating material relevant to learning tasks with reference to sentence construction and word order